Leptin produced by obesity-altered adipose stem cells promotes metastasis but not tumorigenesis of triple-negative breast cancer in orthotopic xenograft and patient-derived xenograft models - Sabol, Rachel A. (Breast Cancer Res, 2019)
BACKGROUND: Breast cancer is the second leading cause of cancer deaths in the USA. Triple-negative breast cancer (TNBC) is a clinically aggressive subtype of breast cancer with high rates of metastasis, tumor recurrence, and resistance to therapeutics. Obesity, defined by a high body mass index (BMI), is an established risk factor for breast cancer. Women with a high BMI have increased incidence and mortality of breast cancer; however, the mechanisms(s) by which obesity promotes tumor progression are not well understood. METHODS: In this study, obesity-altered adipose stem cells (obASCs) were used to evaluate obesity-mediated effects of TNBC. Both in vitro and in vivo analyses of TNBC cell lines were co-cultured with six pooled donors of obASCs (BMI > 30) or ASCs isolated from lean women (lnASCs) (BMI < 25). RESULTS: We found that obASCs promote a pro-metastatic phenotype by upregulating genes associated with epithelial-to-mesenchymal transition and promoting migration in vitro. We confirmed our findings using a TNBC patient-derived xenograft (PDX) model. PDX tumors grown in the presence of obASCS in SCID/beige mice had increased circulating HLA1(+) human cells as well as increased numbers of CD44(+)CD24(−) cancer stem cells in the peripheral blood. Exposure of the TNBC PDX to obASCs also increased the formation of metastases. The knockdown of leptin expression in obASCs suppressed the pro-metastatic effects of obASCs. CONCLUSIONS: Leptin signaling is a potential mechanism through which obASCs promote metastasis of TNBC in both in vitro and in vivo analyses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13058-019-1153-9) contains supplementary material, which is available to authorized users.